Epistemological bases of categorization - Bochkarev, A. Е. (Cognition, Communication, Discourse, 2018)
Many modes of understanding, determined by analysis of the different possible kinds of categorization, such as idea, notion, or concept, show how the world is perceived in any field of knowledge. In this way categorization is a sequence of terms in which each term is related to each other term by the mode of understanding.